STUDENTS KNOWLEDGE REGARDING THE ORAL HEALTH OF THE PATIENT WITH DIABETES - Florinel Cosmin Bida; Dan Nicolae Bosînceanu; Zinovia Surlari; Carina Balcoș; Dragoș Ioan Virvescu; Monica Mihaela Scutariu; Dana Gabriela Budală; Norina Consuela Forna (Romanian Dental Association for Education, 2020)
Introduction. The adhesion of microorganisms and the formation of dental plaque on acrylic denture surfaces are the primary causes of several oral diseases. To form the polymer, PMMA pre polymerized fine particles are mixed with a liquid monomer resulting in chains of polymer. PMMA provisional materials are susceptible to bacterial adhesion and colonization when compared to materials used for final restorations due to the increased surface roughness